The phylogeny of the world's bulbuls (Pycnonotidae) inferred using a supermatrix approach. (23rd February 2017) - Shakya, Subir B.; Sheldon, Frederick H.
Abstract : The bulbuls comprise an ecologically important group of frugivorous, seed‐dispersing birds found in Asia and Africa. Although several studies have examined the phylogenetic relationships of subsets of bulbul species, a comprehensive phylogeny of the family Pycnonotidae has hitherto been lacking. We used publicly available sequences generated from previous phylogenetic studies, augmented by new sequences from several unstudied taxa, to create a supermatrix from which to infer the phylogeny of the family. In all, we compared 121 of the 130 bulbul species. Our tree supports the monophyly of the family and comprises an exclusively African and a predominantly Asian clade. Several genera were found not to be monophyletic and we suggest taxonomic changes to provide a more accurate classification based on phylogeny.